APROXIMATIVE METHODS FOR SOLVING SOME NONLINEAR DIFFERENTIAL EQUATIONS - Kujumdžieva-Nikoloska, Marija; Dimitrovski, Dragan (Matematichki Bilten, 1995)
In this paper we give approximative solutions of some differential equations whose solutions are squares or square roots of the solutions of other differential equations.